Predictors of fear of COVID-19 in a low-income country: health literacy is important - Ranjbaran, Soheila; Chollou, Khalil Maleki; Abedi-Nerbin, Salar; Babazadeh, Towhid (Frontiers in Psychology, 2024)
Introduction: Excessive fear of a threatening condition or situation can result in individuals engaging in unhealthy behaviors, especially during the COVID-19 pandemic. Identifying the influential factors of fear can be effective in designing and implementing health-center interventions to control and reduce the COVID-19 pandemic. Methods: This study was a cross-sectional design implemented in Iran in 2022. Participants were adults 18-65 years of age recruited randomly from primary Health Care Services Centers (HCSCs) by medical records (n=380, 64.7% female, mean (SD) age 32.14 ± 10.98 years) in urban and rural areas of the county. The data collection included a demographic form, Fear of COVID-19 questionnaire, Perceived Barriers of COVID-19 preventive behaviors, Self-efficacy, and Health Literacy for Iranian Adults (HELIA) questionnaire. Results: It was determined that the fear of COVID-19 showed statistically significant differences according to gender (p-value= 0.013), education level (p-value= 0.001), and job status (p-value= 0.001). According to the hierarchical linear regression, educational level ((p-value= 0.001; β= 0.665), job (ß=0.126; p-value=0.018), self-efficacy (p-value= 0.015; β= 0.103), and Health Literacy (HL) (p-value= 0.001; β= 0.446) were significant predictors of fear of COVID-19. Also, among variables, educational level (p-value= 0.001; β= 0.665) and HL (p-value= 0.001; β= 0.446) were the most important predictors for fear of COVID-19. Discussion: This research shows that HL has a potential and determinative role in controlling fear of COVID-19. The findings can help healthy policymakers and healthcare providers design HLbased programs in similar epidemics and pandemic situations.